Bioactives in Chinese Proprietary Medicine Modulates 5α-Reductase Activity and Gene Expression Associated with Androgenetic Alopecia - Tan, Justin J. Y.; Pan, Jing; Sun, Lihan; Zhang, Junying; Wu, Chunyong; Kang, Lifeng (Frontiers in Pharmacology, 2017)
Androgenetic alopecia (AGA) is characterised by a progressive and patterned transformation of thick, pigmented terminal scalp hairs into short, hypo-pigmented vellus-like hairs. The use of Minoxidil and Finasteride to treat AGA are often associated with complications in safety and efficacy. However, herbal remedies are deemed to have lesser side effects in many societies. This study aims to identify potential hair growth properties of individual compounds from a Chinese proprietary medicine known as Yang-xue Sheng-fa Capsules (YSC), used in China for many years for improving AGA. Six marker compounds, including 2,3,5,4 tetrahydroxystilbene-2-O-β-D- glucoside (TSG), Chlorogenic acid, Emodin, Ferulic acid, Isoimperatorin and Paeoniflorin were used for simultaneous HPLC quantification and anti-AGA in-vitro screening. Simultaneous quantification of these components was performed on 75%（v/v）methanol extracts of YSC, using a Welch Ultimate XB-C18 column and gradient elution. Five compounds significantly promoted cell proliferation in cultured immortalised human Dermal Papilla Cells (DPC). Multiple genes associated with the progression of AGA, including IGF-1, DKK-1 and TGF-β1, were found to be regulated by some of these compounds. Interestingly, Ferulic acid and Emodin demonstrated good pharmacological properties against AGA, thereby concluding the potential of these bioactives to be used in the treatment against AGA.